Zona Positif Connected Envieroment Sebagai Pembelajaran Selama Social Distancing - Sutrisno Sutrisno (PERSPEKTIF, 2021)
This study aims to look at the COVID-19 phenomenon that causes changes in the situation, so that general ideas / theories can be concluded. This research is a research journal, the research design uses an explanatory thinking approach which is carried out inductively. This research resulted in the novelty concept of the Positive Connected Environment. Positive Connected Environment is an integration of Social Distancing theory, Motivational Forces, and Stress theory. The dimensions that make up the concept of novelty are being discussed. The conclusion of this study explains that the COVID-19 pandemic has an impact on the world of education, a changing environment where distance learning suddenly creates stress for the elderly. The obligation and responsibility to carry out tertiary tridharma training makes seniors creative to find ways to stay connected with students who are doing distance learning, but with limited mastery of applications. The application of the concept of the Positive Connected Environment model is a solution for lecturers who experience limited mastery of distance learning applications by utilizing face-to-face limitations, simple discussions and applied theory games. The concept of a behavior model in proactive behavior between lecturers and students so as to create a positive zone that is connected to a pleasant environment, without coercion and is able to present a new atmosphere in the learning process.